FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) BAGI AKSEPTOR KB DI PUSKESMAS JAILOLO - Bernadus, Johana D.; Madianung, Agnes; Masi, Gresty (Universitas Sam Ratulangi)
Abstract: One strategy of the implementation of the family planning program stated in the Medium Term Development Plan in 2004-2009 was the increasing use of the long-term contraceptive method (LTM) such as the intra uterine device (IUD). IUD is one type of long term contraceptives that is ideal in order to space pregnancies. This study aimed to determine the factors associated with the selections of IUDs for family planning acceptors in Jailolo Health Center. This was a cross sectional design. The population was all active family planning acceptors in Jailolo Health Center. Sampling was done by using simple random sampling. Data were processed by using univariate, bivariate, and multivariate tests, analyzed with SPSS Ver.20 and chi-square with a significance of α = 0.05. The results showed that based on the bivariate analysis there was a relationship between the variables of age, education, knowledge, service rates, partner approval, and culture with the selection of IUD; while job, economic status, and service rates showed no relationship with the selection of an IUD at the Jailolo Health Center. Multivariate analysis of five related independent variables showed that education was the most dominant in the selection of IUD with P = 0.161. Conclusion: among the active family planning acceptors in Jailolo Health Center from December 27, 2012 until January 19, 2013, age, education, knowledge, service rate, partner approval, and culture were related to the selections of IUDs; and education was the most dominant one. Keywords: factors, selection of IUD. Abstrak: Salah satu strategi pelaksanaan program KB seperti tercantum dalam Rencana Pembangunan Jangka Menengah (RPJM) tahun 2004-2009 ialah meningkatnya penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) seperti IUD (Intra Uterine Device, Alat Kontrasepsi Dalam Rahim, AKDR). AKDR merupakan salah satu jenis alat kontrasepsi jangka panjang yang ideal dalam upaya menjarangkan kehamilan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan pemilihan AKDR oleh akseptor KB di Puskesmas Jailolo. Desain penelitian dengan menggunakan cross sectional. Populasi ialah seluruh akseptor KB aktif di Puskesmas Jailolo 27 Desember 2012 sampai dengan 19 Januari 2013. Pengambilan sampel dilakukan dengan simple random sampling. Data diolah secara univariat, bivariat dan multivariat menggunakan SPSS Ver.20 dengan uji Chi-Square dan kemaknaan α= 0,05. Dari hasil analisis bivariat terdapat hubungan antara variabel usia, pendidikan, pengetahuan, tarif pelayanan, persetujuan pasangan, budaya dengan pemilihan AKDR di Puskesmas Jailolo sedangkan pekerjaan, ekonomi dan tarif pelayanan tidak berhubungan. Hasil analisis multivariat dari lima variabel independen yang berhubungan menunjukkan bahwa pendidikan yang paling dominan dalam pemilihan AKDR dengan nilai P = 0,161. Simpulan: pada akseptor KB aktif di Puskesmas Jailolo 27 Desember 2012 - 19 Januari 2013, faktor usia, pendidikan, pengetahuan, tarif pelayanan, persetujuan pasangan, dan budaya mempunyai hubungan dengan pemilihan AKD; dan yang paling berperan ialah faktor pendidikan. Kata Kunci: Faktor-faktor, Pemilihan AKDR.